The Role of Intrinsic Pathway in Apoptosis Activation and Progression in Peyronie's Disease. (13th August 2014) - Loreto, Carla; La Rocca, Giampiero; Anzalone, Rita; Caltabiano, Rosario; Vespasiani, Giuseppe; Castorina, Sergio; Ralph, David J.; Cellek, Selim; Musumeci, Giuseppe; Giunta, Salvatore; Djinovic, Rados; Basic, Dragoslav; et al.
Abstract : Peyronie's disease (PD) is characterized with formation of fibrous plaques which result in penile deformity, pain, and erectile dysfunction. The aim of this study was to investigate the activation of the intrinsic apoptotic pathway in plaques from PD patients. Tunica albuginea from either PD or control patients was assessed for the expression of bax, bcl-2 and caspases 9 and 3 using immunohistochemistry and by measurement of apoptotic cells using TUNEL assay. Bax overexpression was observed in metaplastic bone tissue, in fibroblasts, and in myofibroblast of plaques from PD patients. Little or no bcl-2 immunostaining was detected in samples from either patients or controls. Caspase 3 immunostaining was very strong in fibrous tissue, in metaplasic bone osteocytes, and in primary ossification center osteoblasts. Moderate caspase 9 immunostaining was seen in fibrous cells plaques and in osteocytes and osteoblasts of primary ossification centers from PD patients. Control samples were negative for caspase 9 immunostaining. In PD patients the TUNEL immunoassay showed intense immunostaining of fibroblasts and myofibroblasts, the absence of apoptotic cells in metaplasic bone tissue and on the border between fibrous and metaplastic bone tissue. Apoptosis occurs in stabilized PD plaques and is partly induced by the intrinsic pathway.